Quality of life in Down syndrome in Brazil: a cross-sectional study - Bermudez, Beatriz Elizabeth Bagatin Veleda; Franklin, Gustavo Leite; Oliveira, Camila Maciel de; Coutinho, Léo; Crippa, Ana Chrystina de Souza (Arquivos de Neuro-Psiquiatria, 2023)
Background Down syndrome is the most commonly genetic cause of developmental delay and intellectual disability, affecting 1:700 live births. It is associated with heart disease and recurrent infections, among other complications that greatly impair the patient's quality of life.Objective To evaluate the major factors associated with quality of life in a cohort of patients with Down syndrome.Methods We assessed 1,187 patients with Down syndrome, older than 4 years old, with an adaptation of the Personal Outcomes Scale validated for Portuguese language, interviewing patients, parents, and caregivers.Results A bad quality of life was reported in 56.4% of the sample. The main factors associated with better quality of life were female sex, first medical visit before 4 months old, higher parental education, a professionally active mother, and prenatal care. The main factors associated with worse quality of life were family history of alcohol abuse and psychiatric disorders and comorbidity with autism and epilepsy.Conclusion Clinical comorbidities such as autism and epilepsy carry a heavy burden among patients with Down syndrome, while factors related to family support, such as employment status and educational background of the parents, enhance quality of life. The factors associated with quality of life among patients with Down syndrome should be adequately evaluated in medical consultation and targeted in public health policies.
Keywords: Down Syndrome; Intellectual Disability; Quality of Life; Comprehensive Health Care